1996
DOI: 10.1073/pnas.93.9.4071
|View full text |Cite
|
Sign up to set email alerts
|

Homophilic adhesion mediated by the neural cell adhesion molecule involves multiple immunoglobulin domains.

Abstract: The neural cell adhesion molecule (N-CAM) mediates homophilic binding between a variety of cell types including neurons, neurons and glia, and neurons and muscle cells. The mechanism by which N-CAM on one cell interacts with N-CAM on another, however, is unknown. Attempts to identify which of the five immunoglobulin-like domains (Ig

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
98
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 36 publications
10
98
0
Order By: Relevance
“…A number of Ig3-specific reagents have been reported to inhibit cellcell aggregation including antibodies, recombinant proteins, and peptides, and it has been proposed that self-association of the Ig3 domains is central to N-CAM binding (15)(16)(17)(18). However, we and others (3,19) have been unable to demonstrate self-association of the isolated Ig3 domain in solution.…”
Section: Resultsmentioning
confidence: 47%
See 3 more Smart Citations
“…A number of Ig3-specific reagents have been reported to inhibit cellcell aggregation including antibodies, recombinant proteins, and peptides, and it has been proposed that self-association of the Ig3 domains is central to N-CAM binding (15)(16)(17)(18). However, we and others (3,19) have been unable to demonstrate self-association of the isolated Ig3 domain in solution.…”
Section: Resultsmentioning
confidence: 47%
“…Independent bead and cell-binding experiments also demonstrated self-association of Ig3. In addition, this study observed reciprocal interactions between the remaining Ig domains consistent with antiparallel binding of all 5 Ig domains (18). In contrast, solution and crystallographic studies have characterized an interaction between the N-terminal Ig domains Ig1 and Ig2 (3, 19 -21), and failed to detect any self-association of Ig3.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…For example, the first and second Ig domains interact with each other promoting neurite outgrowth (Thomsen et al, 1996;Kiselyov et al, 1997;Jensen et al, 1999;Rønn et al, 1999). The third Ig domain seems to bind to itself and is also capable of stimulating neurite outgrowth (Rao et al, 1992Sandig et al, 1994;Ranheim et al, 1996). The fourth Ig domain is involved in interaction with another NCAM, L1, and contains an alternatively spliced 10 amino acidlong sequence termed VASE, which when expressed abrogates the neurite outgrowth-promoting activity of NCAM (Small and Akeson, 1990;Saffell et al, 1994;Lahritz et al, 1997).…”
mentioning
confidence: 99%